In Silico Analysis of Metabolite Compounds from the Essential Oil of Cinnamomum burmannii Bark with COX-1 and COX-2 as Target Molecules - Budiastuti, Budiastuti; Helmi, Vitra Nuraini; Effendi, Mustofa Helmi; Plumeriastuti, Hani; Khairullah, Aswin Rafif; Ugbo, Emmanuel Nnabuike; Tyasningsih, Wiwiek; Awwanah, Mo; Pratama, Bima Putra; Prasetyo, Agung; Moses, Ikechukwu Benjamin; Ahmad, Riza Zainuddin (Trends in Sciences, 2025)
In silico approaches, including molecular docking, have emerged as powerful tools in predicting the interaction between natural compounds and molecular targets such as COX-1 and COX-2. These computational methods provide valuable insights into the binding affinity and selectivity of these compounds, making them indispensable in modern drug discovery. The interactions between metabolites from C. burmanii essential oil and COX-1 and COX-2 were investigated through in silico analysis. This analysis involves several stages, including In Silico Activity Analysis, Drug-likeness Test, Anti-inflammatory Agent Probability, and Molecular Docking. The study suggests that specific compounds could serve as anti-inflammatory adjuvants alongside conventional anti-inflammatory drugs (NSAIDs), potentially reducing dosages or minimizing the side effects associated with NSAID use. The in silico analysis results obtained by simulating the binding of metabolites with COX-1 and COX-2 target proteins using PyRx 0.8 software indicated that 12 out of 14 volatile oil metabolites might contribute to anti-inflammatory activity. However, the anti-inflammatory effects of cinnamon oil require further validation through in vivo testing. HIGHLIGHTS This article focused on in silico approaches in predicting the interaction between natural compounds and molecular targets such as COX-1 and COX-2. In silico approaches provide valuable insights into the binding affinity and selectivity of COX-1 and COX-2. Cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) are enzymes that play a significant role in biological response, particularly in inflammation. The major role of Cinnamomum burmannii essential oil is to selectively inhibit COX-1 and COX-2, potentially offering a natural alternative for inflammation management with reduced side effects compared to conventional NSAIDs. GRAPHICAL ABSTRACT